Innovation and Competitive Advantage: A Case Study on "Jago" Mobile Coffee in South Tangerang - Puja Sagita; Siska Yulia; Sudarmiatin Sudarmiatin; Trisetia Wijijayanti (Greenation International Journal of Economics and Accounting, 2024)
This study examines innovation and competitive advantage in the mobile coffee business Jago operating in South Tangerang, as a response to the growing intensity of competition in the coffee industry and the changing behavior of urban consumers. The purpose of this research is to explain the forms of innovation developed and how these innovations contribute to competitive advantage. The study uses a qualitative approach with data collected through observations, in-depth interviews with owners, baristas, and customers, as well as field documentation. The results indicate that Jago Coffee has successfully implemented innovation in product quality, service systems, operational processes, and business model design. These innovations provide consistent product quality, technology-based service convenience, operational efficiency through a mobile café concept, and enhanced accessibility through flexible mobility. The findings confirm that innovation plays a crucial role in strengthening the competitive position of Jago Coffee in South Tangerang. This research contributes to the development of innovation studies in small businesses operating with high mobility in the digital economy era.